2011
DOI: 10.1021/ja109824x
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Calcium VAPOL Phosphate Mediated Asymmetric Chlorination and Michael Reactions of 3-Substituted Oxindoles

Abstract: We disclose a novel high yielding and highly enantioselective chiral calcium VAPOL phosphate-catalyzed chlorination of 3-substituted oxindoles with N-chlorosuccinimide (NCS). The reaction conditions are also shown to be effective for the catalytic enantioselective Michael addition of 3-aryloxindoles to methyl vinyl ketone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(47 citation statements)
references
References 59 publications
0
47
0
Order By: Relevance
“…Oxindoles with a heteroatom at the C‐3 position have received considerable attention owing to their potential applications in medicinal chemistry 1gm. Recently, various methods for the asymmetric synthesis of 3‐fluorooxindoles,4 3‐chlorooxindoles,5 3‐aminooxindoles,6 and 3‐hydroxyoxindoles7 have been reported. Many oxindoles with a thio group at the carbon stereocenter have been found to have anticancer, antifungal, or antitubercular activities 1k–m.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxindoles with a heteroatom at the C‐3 position have received considerable attention owing to their potential applications in medicinal chemistry 1gm. Recently, various methods for the asymmetric synthesis of 3‐fluorooxindoles,4 3‐chlorooxindoles,5 3‐aminooxindoles,6 and 3‐hydroxyoxindoles7 have been reported. Many oxindoles with a thio group at the carbon stereocenter have been found to have anticancer, antifungal, or antitubercular activities 1k–m.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, 3-aryloxindoles 1 e-h were found to be more reactive precursors for the sulfenylation reaction. The corresponding reactions were completed within a shorter time (6 h) giving the products 3 e-h in excellent yields (91-98 %) and high enantioselectivities (85-87 % ee; Table 2, entries [5][6][7][8].…”
mentioning
confidence: 99%
“…A plied chiral calcium VAPOL phospate 11 as a catalyst for chlorination with NCS. [21] The reaction afforded the desired products with excellent enantioselectivity (Scheme 15). A dramatic drop in enantioselectivity occurred when 3-methyloxindole was used as the substrate in both catalyst systems (7 % ee with 10/nickel(II) and 62 % ee with 11).…”
Section: Entry Catalyst/conditions [A]mentioning
confidence: 99%
“…Several electron-donating and withdrawing aromatic enamides were tested, and the enantioselectivites of the desired 2-hydrazinoketones and 1,2-diamines were high. Antilla et al reported chiral calcium VAPOL phosphate-mediated asymmetric 1,4-addition reactions of 3-substituted oxindoles (Table 13) [59]; for reviews of asymmetric reactions of oxindole, see [60][61][62][63]. It was showed that VAPOL phosphate could be applied, and the desired products were obtained in excellent yields with high enantioselectivities.…”
Section: Asymmetric Aldol and Related Reactionsmentioning
confidence: 99%